Combination of Technology Acceptance Model and Decision-making Process to Study Retentive Consumer Behavior on Online Shopping - Rudini, Edwin; Riana, Dwiza; Hadianti, Sri (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
During the spread of the Covid-19 virus, generally the Indonesian people began to switch from conventional markets to buying and selling goods and services online with various features and conveniences offered to users. The purpose of this study is to find out the extent to which indicators of satisfaction and trust influence consumer attitudes and behavior when deciding to make transactions at online shops. The study method uses a combination of TAM (Theory Acceptance Model) and DMP (Decision Making Process) models using a sampling of 110 student respondents and the public who have made transactions in online shops. Data analysis using SEM (Structural Equation Modeling) theory. The results showed that satisfaction and trust will influence consumers in shaping.